Epidemiological trends and disparities in iodine, vitamin A, and iron deficiencies among children aged 0–14 years globally, 1990–2021 - Peng, Fang; Lin, Xiaojuan; Liu, Shanshan; Zou, Hui; Yi, Canhong; Tian, Yuquan (Frontiers in Nutrition, 2025)
BackgroundNutritional deficiencies in iodine, vitamin A, and iron remain major public health challenges for children under 15 years, impairing growth, cognitive development, and long-term health outcomes. Despite global interventions, disparities persist across socioeconomic strata. This study evaluates trends, regional variations, and sociodemographic correlates of these deficiencies from 1990 to 2021.MethodsData from the Global Burden of Disease 2021 database were analyzed for 204 countries, focusing on children aged 0–14 years. Age-standardized incidence rate, DALYs, and SDI correlations were assessed using Expected Annual Percentage Change (EAPC) and Bayesian age-period-cohort models to project trends to 2050.ResultsFrom 1990 to 2021, iodine deficiency incidence rate declined by 92.9% (EAPC: −0.04), with DALY rates dropping 98.7%. Vitamin A deficiency incidence rate decreased by 94.9% (EAPC: −2.02), while DALY rates fell 92.8%. Dietary iron deficiency DALY rates remained stable (EAPC: 0.53). Low SDI regions exhibited 7.3 × higher iodine and 151 × higher vitamin A deficiency DALY rates than high SDI regions. Projections indicate sustained declines for iodine and vitamin A deficiencies but stagnation in iron deficiency, particularly in conflict-affected areas.ConclusionWhile iodine and vitamin A deficiencies have significantly reduced globally, dietary iron deficiency persists in low SDI regions. Tailored interventions, including fortification programs and health system strengthening, are critical to addressing inequities and achieving global nutrition targets.